Undang-Undang Simbur Cahaya dalam Mengatur Hukum Perkawinan di Kesultanan Palembang - Dwi Anggi Wulandari; Marzuki Marzuki (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
The purpose of writing this article is to find out the Simbur Cahaya Law in regulating marriage law in the Palembang Sultanate. In this paper the author focuses on the Marriage Law in Palembang, because many people in Palembang currently use the marriage law that existed during the Palembang Sultanate. The use of marriage law in the Palembang Sultanate was used to preserve the noble cultural values that have existed since ancient times. The cultural values contained in the marriage law in the Palembang Sultanate are currently dynamic, adjusting to the existing conditions in the Palembang community. This article was compiled using the library research method, which is a method of collecting data by utilizing sources and library materials. The result of the conclusion obtained is that the Simbur Cahaya Law is a law that adapts Islamic and customary law. On the initiative of Ratu Sinuhun, the law was made as a general rule in all the Palembang residences. The law contains regulated public relations including regulations in the field of marriage and single girl, clan, village and farming, clan, and punishment. The marriage ceremony ceremony in the Sultanate of Palembang is explained in the Simbur Cahaya Law in the first chapter which explains the custom of single and married women is in article 1, article 4, article 5, article 12, article 13, and article 14 which explains how ethics in good relations men and women, and marriage. The stages of the traditional wedding ceremony are: 1) before the wedding, namely madik, menyenggung, meminang atau ngelamar, berasan, mutus kato; 2) the implementation of marriage; and 3) after marriage.